Effects of Teacher Enthusiasm and Type of Text on the Motivation and Achievement of Schoolchildren - Valentín, Alberto; Mateos, Pedro M.; González-Tablas, Maria Mar; López, Estrella (Frontiers in Psychology, 2022)
This study aims to analyze the effects of teacher enthusiasm and type of text on student motivation and achievement. The participants were 369 elementary school students. We used four videos showing a teacher presenting two texts (narrative or descriptive) in two conditions of enthusiasm (high or neutral). A MANOVA revealed additive effects due to enthusiasm and text type on motivation and achievement, but no interaction. Mediation analyzes indicated that enthusiasm showed direct and indirect effects through motivation only for descriptive text. Therefore, the motivational mediation between teacher enthusiasm and student achievement could be especially important when the text is descriptive.